2021
DOI: 10.28982/josam.930254
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and fibrinogen-to-albumin ratios may be indicators of worse outcomes in ICU patients with COVID-19

Abstract: to-lymphocyte and fibrinogen-to-albumin ratios may be indicators of worse outcomes in ICU patients with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Although these data were not calculated for every patient, they suggest that the neutrophil-to-lymphocyte ratio increased in patients who died. Atlas et al investigated COVID-19 patients who were followed-up in the intensive care unit, and they showed that an increase in the neutrophil-to-lymphocyte ratio, ddimer, and CRP levels was associated with an adverse outcome [22]. In our study, an increase in neutrophils, d-dimer, and CRP and a decrease in lymphocyte levels were observed after CP in patients who died, which is consistent with Atlas et al's results.…”
Section: Discussionsupporting
confidence: 91%
“…Although these data were not calculated for every patient, they suggest that the neutrophil-to-lymphocyte ratio increased in patients who died. Atlas et al investigated COVID-19 patients who were followed-up in the intensive care unit, and they showed that an increase in the neutrophil-to-lymphocyte ratio, ddimer, and CRP levels was associated with an adverse outcome [22]. In our study, an increase in neutrophils, d-dimer, and CRP and a decrease in lymphocyte levels were observed after CP in patients who died, which is consistent with Atlas et al's results.…”
Section: Discussionsupporting
confidence: 91%
“…It is stated in accordance with similar research. 16 In conclusion, we can say that the obtained results are in accordance with the expected, i.e. pathophysiological processes in critically ill patients with COVID-19 infection in ICU.…”
Section: Discussionsupporting
confidence: 85%
“…[7] Numerous studies have reported that the fibrinogen-albumin ratio is closely associated with the disease course and mortality in COVID-19 cases. [8][9][10][11] The immune system and nutritional level are closely linked to an individual's susceptibility to infections. Although hypoalbuminemia occurs in cases of inflammation and malnu-trition, lymphopenia is one of the most common laboratory findings in acute viral infections.…”
Section: Introductionmentioning
confidence: 99%